THE EFFECT OF RELIGIOSITY, BRAND IMAGE AND WORD OF MOUTH ON CUSTOMER'S DECISION TO APPLY FOR INSURANCE PT PRUDENTIAL UNIT SYARIAH - Neng Auliya Rohimatul Ummi; Nining Nurhasanah; Donny Setiawan (Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to analyze the effect simultaneously and partially between the variables of Religiosity, Brand Image, and Word of Mouth on the customer decision process in applying for prudential sharia insurance. This research is quantitative. The data used are primary data by distributing questionnaires to 100 respondents and secondary data obtained by conducting a literature study. Sampling was done by using a quantitative purposive sampling technique. The data analysis method uses multiple linear regression. The results of this study indicate that there is a simultaneous influence on the variable Religiosity, Brand Image, and Word of Mouth on the customer decision process. The results of this study also indicate partially that Religiosity, Brand Image, and Word of Mouth significantly influence customer decision processes. The results of the determination show that the customer decision process can be explained by the variable Religiosity, Brand Image, and Word of Mouth by 31.1%. This means that there is a 68.9% (100% -31.1%) variance of the dependent variable explained by other factors not included in this study.